Metaphors of Globalization
XI, 291 p.
Keywords: By revisiting globalization using an analysis of metaphors, such as 'global village' and 'network society', this volume sheds new light on overlooked dimensions of global politics, redresses outdated conceptualizations, and provides a critical analysis of existing approaches to the study of globalization.